Enhancing Most Essential Learning Competency (Melc) in English 9 Using The Skills-Based Learning Material (Faculty of Teacher Training and Education, Universitas Terbuka, 2021)
The skills-based learning material was made and studied by the researcher due to sudden changes in education in a time of the pandemic. The main focus of this study is to determine the effectiveness of the skills-based learning material for English 9. This study used the pretest-posttest non-equivalent control group design, which falls under the quasi-experimental design. On the test of significant difference between the formative mean scores of the experimental and comparison groups, it was found out that the formative tests had a significant effect on the respondents' learning performance at p 0.01 level. Additionally, the posttest mean scores of each group; got the 0.01 level of significance, as well as the pretest and posttest mean scores of each group. Moreover, based on the computed Cohen's d value of 1.16, the effect size of the learning material to the students' performance is large compared to the comparison group that shows a small effect size at 0.31 Cohen's d value. Generally, there is a significant difference between the formative test of the two groups with the average and high mean scores, respectively. There is also a significant difference between the posttest mean scores of the two groups and as well between the pre-test and post-test mean scores. Moreover, Cohen's effect size value of 1.16 suggested a large effect of the material on the respondents' learning performance. As for recommendations, there is a need for the teacher to incorporate the 21st Century Skills into learning competencies.